MYOCARDIAL INFARCTION RATES DURING THE PANDEMIC AND THE PRE-PANDEMIC PERIOD (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The recent and ongoing coronavirus pandemic has taken over almost the entire world. Despite the severity of the COVID-19 problem, mortality from this disease is in no way comparable to mortality from cardiovascular disease (CVD), which remains the leading cause of death among the population. Of course, the increase in mortality directly and indirectly depends on the clinical forms of this virus